The Impact of Changes in External Factors on the World Vegetable Oil Market - Purba, Helena J.; Sinaga, Bonar M.; Novianti, Tanti; Kustiari, Reni (International Journal of Economics and Financial Issues, 2018)
Vegetable oil is an important commodity that functions as food, feed and fuel. Palm oil, soybean oil, rapeseed oil and sunflower oil are the main vegetable oils (90%) traded on the world market. Changes in external factors allegedly affect the performance of exports and imports of each type of vegetable oil on the world market. This study aims to analyze the impact of changes in external factors (increase in world prices of crude oil and demand for vegetable oils) on the world trade performance of vegetable oil.Analysis using econometric models in the form of simultaneous equations consists of 45 structural equations and 8 identity equations which are estimated by the Two Least Square (2SLS) method using the annual data series 1991-2015. Simulation method with Newton method, the results of the study showed that the increase in world prices of crude oil has a positive impact on improving the performance of the trade in palm oil, rapeseed oil and sunflower oil, but the trade performance of soybean oil has declined. Imports of Chinese palm oil experienced the highest increase of 9.53%. Palm oil exports from Indonesia and Malaysia have increased, but the increase is smaller than the increase in palm oil imports from China, Europe, the United States and India so that the world price of palm oil is still increasing.The increasing GDP of the United States has the greatest impact on exports, imports and prices of world palm oil. While the increase in China's GDP has the most impact on imports and world prices of rapeseed oil. Keywords: Vegetable Oil, Trade, External Factors, Crude Oil JEL Classification: F10 DOI: https://doi.org/10.32479/ijefi.7069